Technology dissemination for the home industry of Tahu Takwa Bintang Al Qomar to improve the efficiency of the soybean milling process - Mujahid Wahyu; Devina Rosa Hendarti; Ahmad Dony Mutiara Bahtiar (Universitas Muhammadiyah Magelang, 2022)
The efficiency of the production process in the home industry 'Tahu Taqwa Bintang Al Qomar' is a major issue, particularly in the soybean milling process. According to the owner, this procedure should be carried out elsewhere. The purpose of this program is to improve the efficiency of the soybean milling process, which is the primary source of tofu. Methods of this program include: 1) design of soybean grinding machine; 2) manufacture of design for soybean grinding machine with a capacity of 10 kg; 3) machine testing; and 4) training and assistance in operating the equipment to partners. The result of this community service activity is a soybean grinding machine product as a solution to partner problems, as well as increasing partner skills, especially in operating machines. This is to support the soybean milling process independently, so as to achieve the efficiency of the soybean milling process as a raw material for tofu.